Geographical Knowledge and Mineral Riches in the Struggle for Sovereignty and Possession of Southern Brazil (1750-1755) - Moura, Denise [UNESP] (Modern Humanities Research Association, 2019)
The construction of Portuguese sovereignty on the lands of southern Brazil in the eighteenth century triggered a dispute between the Portuguese Crown and the sertanistas (backwoodsmen), who both supported their arguments for rights to the lands with documents, such as manuscripts and maps, which confirmed that they had geographical knowledge of the area. The starting point of this dispute was when a geographer from Genoa, Francesco Tosi Colombina, was hired by the Portuguese Crown to write a manuscript plan to explore the Sertoes do Tibagi in 1752, whose repercussion was to prompt the sertanista Angelo Pedroso to order a map of the same lands and put in question the Italian-sertanista cartography.
Keywords: State; sovereignty; rights of states; boundaries; territorial rights; geography; cartography; maps; geographers; geographical exploration; mineral resources; southern Brazil; wilderness